Difusi Inovasi DJBC dalam Menerapkan Pelayanan e-CD di Penerbangan Internasional Bandara Kualanamu Medan - Syafruddin Pohan; Muhammad Tarmizi; Wanti Isadora Simbolon (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Technology that continues to develop has encouraged various agencies and companies to transform towards the digital era, one of which is the Directorate General of Customs and Excise (DJBC). The internet-based application Electronic Customs Declaration (e-CD) developed by DJBC, is an information that transforms the Customs Declaration form which was previously filled out manually on paper by international passengers at a number of international airports in Indonesia, one of which is Kualanamu Airport. . This research aims to determine the application and impact of the innovation diffusion of the Customs and Excise Supervision and Services Office (KPPBC) Type Madya Customs B Kualanamu in applying electronic customs declaration services on International Flights at Kualanamu Airport, Medan. The methodology used in this research uses library or literature studies by collecting, reading, evaluating and analyzing various references such as books, journals and other literature that are relevant to the topic of this paper. The results of this research show that the application of e-CD can make the customs process easier on arrival to Indonesia, especially at Medan's Kualanamu Airport, to be more efficient because it no longer uses a piece of paper as was done previously.